2019
DOI: 10.3389/fncel.2019.00420
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-P2X7 Signaling Pathway Participates in the Regulation of Slit1 Expression in Satellite Glial Cells

Abstract: Slit1 is one of the known signaling factors of the slit family and can promote neurite growth by binding to its receptor, Robo2. Upregulation of Slit1 expression in dorsal root ganglia (DRG) after peripheral nerve injury plays an important role in nerve regeneration. Each sensory neuronal soma in the DRG is encapsulated by several surrounding satellite glial cells (SGCs) to form a neural structural unit. However, the temporal and spatial patterns of Slit1 upregulation in SGCs in DRG and its molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…It has repeatedly been suggested that neuronal P2X7Rs may be absent or down-regulated at resting conditions but become expressed on stressful conditions such as temporal lobe epilepsy (Engel et al, 2012 ; Jimenez-Pacheco et al, 2016 ), ischemic damage to the brain (Franke et al, 2004 ), neuropathic pain (Andó and Sperlagh, 2013 ; Zhang et al, 2019 ), and neurodegenerative diseases (AD; Diaz-Hernandez et al, 2012 ; Rodrigues et al, 2015 ; Huntington’s disease and PD, Diaz-Hernandez et al, 2009 ; Glaser et al, 2020 ; MS, Sharp et al, 2008 ; Grygorowicz et al, 2010 ). Without any doubt these injurious conditions activate microglial cells as well as astrocytes/oligodendrocytes and facilitate the release of neurodamaging signaling molecules (cytokines, chemokines, reactive oxygen and nitrogen species, glutamate/ATP), possibly facilitating neuronal functions.…”
Section: Neuronal P2x7 Receptors Per Se ?mentioning
confidence: 99%
“…It has repeatedly been suggested that neuronal P2X7Rs may be absent or down-regulated at resting conditions but become expressed on stressful conditions such as temporal lobe epilepsy (Engel et al, 2012 ; Jimenez-Pacheco et al, 2016 ), ischemic damage to the brain (Franke et al, 2004 ), neuropathic pain (Andó and Sperlagh, 2013 ; Zhang et al, 2019 ), and neurodegenerative diseases (AD; Diaz-Hernandez et al, 2012 ; Rodrigues et al, 2015 ; Huntington’s disease and PD, Diaz-Hernandez et al, 2009 ; Glaser et al, 2020 ; MS, Sharp et al, 2008 ; Grygorowicz et al, 2010 ). Without any doubt these injurious conditions activate microglial cells as well as astrocytes/oligodendrocytes and facilitate the release of neurodamaging signaling molecules (cytokines, chemokines, reactive oxygen and nitrogen species, glutamate/ATP), possibly facilitating neuronal functions.…”
Section: Neuronal P2x7 Receptors Per Se ?mentioning
confidence: 99%
“…In the case of the Slit family, it has been observed that Slit2 is upregulated after rat sciatic nerve transection, but not after crush, localizing in Schwann cells [ 196 ]. Slit1 is upregulated after sciatic nerve transection [ 197 ] and crush [ 198 ], while no changes are detected after dorsal rhizotomy [ 197 ]. In DRG cells, a biphasic expression is reported for Slit1, 2, and 3 after adult mouse sciatic nerve transection, with an initial downregulation, followed by a subsequent upregulation [ 165 ].…”
Section: Guidance Cues In Axotomy and Axon Regenerationmentioning
confidence: 99%
“…In the presence of trauma, ischemia, hypoxia, and inflammation, damaged cells release ATP in large quantities, increasing the extracellular concentrations of this molecule [ 8 ]. This leads to an alteration in energy metabolism and inflammatory processes, since neurons, astrocytes, microglia, and endothelial cells have ATP receptors on their membranes, which mediate the processes of neuronal inflammation and death [ 9 18 ]. In an oxidoreduction equilibrium, ATP plays a double role, depending on its cellular location.…”
Section: Introductionmentioning
confidence: 99%